EFEKTIFITAS PELAKSANAAN RESCHEDULING DALAM PENANGANAN PEMBIAYAAN MURABAHAH BERMASALAH DI BTN SYARIâAH KANTOR CABANG BOGOR - Herdiana, Mia (IAIN Tulungagung, 2018)
Abstract. Rescheduling of murabahah bill on islamic (sharia) bank allegedly making additions to the amount of remaining bills whose purpose is not clear and belongs to the category of usury. Rescheduling is a rescue action that undertaken by bnks to overcome the risk of problem financing. This study airms to determine the effectiveness of rescheduling implementation which is conducted by BTN Sharia Bogor brach office in handling the problematicfinancing. Especially in murabahah financing, either at the stage of analysis of prospetive brrowers before applying for financing, at the time of problem financing happens, and handling financing problems with restructuring-in this case is rescheduling. Method used in this research is a qualitative method with a descripsion analysis as an approach. Literatur review, observation, and interview are used as a way of data collecting. The result of this research shows that first, the rescheduling of murabahah bill of BTN ShariaBogor Branch Office represents the creation of new contract of rescheduling clled adendum akad, while the old contract was no longer valid. Secondly, the BTN Sharia Bogor Branch Office imposes on retardation (taâzir) and compensation costs (taâwidh).